2009
DOI: 10.1007/s10654-009-9355-6
|View full text |Cite
|
Sign up to set email alerts
|

History of allergic disease and epilepsy and risk of glioma and meningioma (INTERPHONE study group, Germany)

Abstract: The aim of the present analysis was to examine the association of a medical history of asthma, hay fever, eczema, or epilepsy with the risk of glioma and meningioma. Data of a German population-based case-control study included 381 meningioma cases, 366 glioma cases, and 1,494 controls. Participants' histories of asthma, hay fever, eczema, and epilepsy and the respective ages at onset were asked during a personal interview. A small inverse association between allergic condition and both glioma (odds ratio: 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
75
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 30 publications
8
75
1
Order By: Relevance
“…Our results support those from case-control studies based on self-reported allergic diseases (5-7, 16, 17, 28-32) and especially those of one case-control study using IgE measurement at the time of tumour diagnosis (19). In two case-control studies, associations between age at onset or duration of allergies (in years) and glioma risk were investigated using questionnaire data, but with conflicting results (16,18). In one cohort study (10), a reanalysis of data from individuals who reported allergies 5 years before a diagnosis of brain tumours were similar to results of the whole cohort.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our results support those from case-control studies based on self-reported allergic diseases (5-7, 16, 17, 28-32) and especially those of one case-control study using IgE measurement at the time of tumour diagnosis (19). In two case-control studies, associations between age at onset or duration of allergies (in years) and glioma risk were investigated using questionnaire data, but with conflicting results (16,18). In one cohort study (10), a reanalysis of data from individuals who reported allergies 5 years before a diagnosis of brain tumours were similar to results of the whole cohort.…”
Section: Discussionsupporting
confidence: 80%
“…The ImmunoCap test (Pharmacia AB, Uppsala Sweden) is one of the standardized tests for atopy in medical diagnostics (25,26), covering about 70-80% of the most common eight inhalant allergens in Europe. In addition, there is no evidence that the specific IgE concentration is influenced by gender and also the lower OR observed by Berg-Beckhoff et al (18) in children with a history of allergy compared with adults have not been confirmed until now. The IgE categories are known to be very stable in blood samples over 17 years (23) without any apparent degradation of IgE-defined allergies.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…As the association was observed also for epilepsies occurring more than a decade before the diagnosis of glioma, the authors suggested that this might indicate an etiological role of epilepsy, or a relatively long preclinical state [808]. This finding and reasoning is consistent with the recent suggestion that chronic latent T. gondii infection of the central nervous system may be responsible for development of ependymoma and glioma [809].…”
Section: Diabetes Mellitus Comorbidities Possible Association Betweensupporting
confidence: 79%